Malaysian reality tv: between myth and reality - Juliana Abdul Wahab, (Universiti Kebangsaan Malaysian, 2010)
The privatization policy that was introduced in 1983 by the Mahathir administration opened up the flood gates for the establishment of TV stations run on a commercial basis as well as for Malaysian media practitioners to produced more local programmes. However,most of the locally produced programmes tend to be mere copies of the western genres.The popularization of these genres is also an indicative of the process of the globalization that has taken place. Since 2000, Malaysian television industry has witnessed the mushrooming of a ‘new’ television genre called reality TV. The ‘new’ genre was popularized by the introduction of reality TV game shows,namely Survivor and Amazing Race, which received favourable response from the Malaysian audiences. Subsequently, Malaysian’s first version of reality game show, Explorace was introduced on TV3. The phenomenon spreads rapidly in the later years. Satellite TV station Astro, on its part, has redefined and introduced a version of musical type reality TV, Akademi Fantasia which become a huge craze in Malaysia. Since then, more and more so-called reality TV shows within the musical programmes have inundated almost every local television channel. The study attempts to trace the development of locally produced reality TV shows and to assess this phenomenon within the context of the Malaysian television industry and within the process of globalization. Equally important, the study seeks to uncover the myth and reality of the new genre